As atividades logísticas no contexto da Gestão da Cadeia de Suprimentos (SCM) - Marchesini, Márcia Maria Penteado (2011)
From the Supply Chain Management (SCM), the logistic function expands its scope within the company, going to exert or support the management and operation of key business processes. Its performance leaves to reduce only the functional sphere ( silo or vertical area ), passing to reach horizontal sphere in such processes. Various sources of literature indicate changes in the logistic function but not characterize precisely or discuss the changes in its scope within the company. In particular, the benefits generated by the involvement of the logistic function on key business processes of SCM have been identified in the literature, but were not identified logistic activities that must execute in each of the processes so that these benefits are achieved. In front of this theoretical gap, the objective of this doctorate thesis was to propose logistic activities necessary for the efficacious operation of key business processes of SCM, generating a conceptual framework that assists in implementing these activities. Such a framework is a guide that can help companies identify, characterize and select the activities that the logistic function can develop in their key business processes. More specifically, this conceptual framework presents, besides the own logistics activities, a way of characterizing these activities, according to four criterions: a) obligatoriness of existence in the company (basic or optional), b) impact on the generation of value (efficiency, efficacy and/or differentiation), c) impact on the dimension of logistic service, d) the integration and coordination with other areas or processes. This thesis used the approach of qualitative research, of descriptive character, of exploratory nature and with experimental study of field. The research method was the multi-case study and the mechanism of data collection was the personal interview realized by a semi-structured questionnaire. This research is also of theoretical-conceptual nature, because it developed a conceptual framework generated from the theoretical review. In three case studies realized, observed consistency in the proposed logistic activities and in its form of characterization. Among the 25 proposed activities, the Company 1 realizes 21 of them, the Company 2 realizes 23 activities and the Company 3 realizes all 25 activities, and all interviewed declared that the set of these proposed activities was complete and consistent.